Pengembangan Sikap Empati Perawat Dalam Patient Center Care Melalui Kepemimpinan Transformasional: Literatur Review - Yetti Oktaviana; Luky Dwiyantoro (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2018)
Introduction: Patient-Centered Care (PCC) is a new paradigm in health services that places patients as the center of care. PCC involves the concept of caring, sharing, communication and building therapeutic relationships. Many patients found complaints about the attitude of nurses who were less friendly in serving, nurses responded less well to complaints felt by patients, nurses did not respond appropriately to the questions submitted by patients, and did not care about the needs of patients. The meaning of nursing practice that supports quality nursing is meeting the needs of patients through interactions based on caring, empathy, responsibility, and respect for the existence of patients. According to patient-centered theory (also known as client-centered theory), one of the factors that influence PCC is empathy. Objective: To provide an overview of the development of nurse empathy in supporting patient-focused services (Patient-Center Care) through transformational leadership. Method: Literature review by searching several research journal articles published through the electronic data base. The electronic data base used: PubMed, EBSCO and Cochrane Library by using keywords: patient center care, empathy, and leadership transformation. As well as using the nursing handbook reference. Results: Increasing empathy can lead to increase in communication and therapeutic relationships between nurses and patients. Empathy is built to support the improvement of patient center care services and patient outcome repair. Efforts to develop empathy attitudes are developed within the framework of transformational nursing leadership. Conclusion: Measurements of empathy and service outcome are used as measurements for evaluating the quality of nursing services. Transformational nursing changes the mindset of what patients expect in services and determines the process for achieving service goals. Always develop adaptive processes and influence staff to achieve service goals